(3cd jhe fHjs (3eUWaj eMehOs - (3eMehO, eUWajs ((3GdbGgQg (B[ (3eUQ (B]s (3OGQ OjjQ ddfTQs, 2019)
(3QMdI WhjdI JHOC deG gHWhG efgG ddCQV, JNjd faSc hbO UGMHJ SjOfG TjK h TGQcJ aj YedjI EYeGQ GdCQV, h Cfc QGabJ EOQjS Ydjg GdSdGe aj QMdJI aj HfGA GdeOf, h ef Ke fLhJ ef GdWhaGf GdYXje GdPj ZWj GdCQV h dLCJ dadc fhM , hQCjJ fGbI JNQL ef bdH GdLHd , h YGUQJ GdUjMI h ZjQgG ef eG fGdJ GdCbhGe GdZGHQI ef YPGH Cdje , h YTJ eY SjOfG EHQGgje Ydjg GdSdGe , h QCjJ GdfhQ GdPj GfHKb ef Hjf KfjGJg djYe GdCQV , hh ef Ke JQj WadG HOjYG eQejG aj HFQ, h JUWMHg deUQ , ajUjQ YRjR eUQ HYO Pdc , Ch Gfc bO hbaJ CeGe GdHMQ h gh jfTb ajUjQ cGdLHdjf jeQ ef HjfgeG GdjghO Hjhe GdRjfI h hLOJ YUG YGOjI ddZGjI JJMhd dKYHGf VNe, h JNjd Ef cfJ eecf cGfhG jMVQhf eLdS Gdedc SdjeGf YdjI GdSdGe , h CeGec h aj ZeVI Yjf jMVQ YQT HdbjS GdYXje CeGec, Ch Cfc YGUQJ Bd YeQGf h JHGQcJ Hge aj eOjfJc , Ch Cfc QCjJ GdeGFOI JgHW ef GdSeGA HgG cd eG WGH h dP, gdj JNjdJ cd gPG ?(B!. (3eQMHG Hc Ydj eJf QMdI CJefGgG TjbI, QMdg GdfhQ hUhdG dgGgfG, GdQMdI GdJj de JfJgj, GdQMdI GdJj eG dHKJ Cf HOCJ MJi SWYJ HGdbdhH TehS JgJOj HgG GdfahS hSW GdXdeIs
11
Keywords: (3ebGdGJ YQHjIs